In Vitro Investigation of Perfluorooctane Sulphonate and Perfluorooctanoic Acid on Boar Spermatozoa Agglutination - Paola Berenice Ortiz‐Sánchez; Yolitzin A. Miranda‐Ruiz; Leslye Sámano‐Hernández; Irma Jiménez‐Morales; Humberto González‐Márquez; Reyna Fierro (Veterinary Medicine and Science)
ABSTRACT Various toxic agents are associated with male infertility, including perfluoroalkyl substances (PFAS), which are emerging as significant contributors due to their physico‐chemical properties that exhibit a propensity for bioaccumulation and potentially pose reproductive risks. The aim of this study was to analyse the effects of perfluorooctane sulphonate (PFOS) and perfluorooctanoic acid (PFOA) on boar spermatozoa during capacitation through a focus on agglutinate formation. A second objective was to assess the influence of d‐penicillamine (d‐Pen) on boar spermatozoa agglutinate prevention. PFOS and PFOA in sublethal concentrations reduced the proportion of spermatozoa that achieved capacitation, PFOS increased to 35% the spermatozoa mortality and both toxic compounds generated an abnormally excessive increase in rosette‐type agglutinates that formed non‐mobile aggregates (only vibrant), like those that form during physiological capacitation. This increase in agglutinates came at the expense of available free spermatozoa for fertilisation. Treatment with d‐Pen, however, significantly reduced rosette formation by PFAS. Further study of the underlying mechanisms revealed that exposure to PFOS and PFOA led to decreased free sulfhydryl (SH) groups on the surface of the spermatozoa, likely due to oxidation caused by the PFAS. Administering d‐Pen also reversed this effect, suggesting a possible involvement of S–S bond formation during spermatozoa agglutination. These findings not only shed light on how PFOS and PFOA affect boar spermatozoa capacitation, but also shows the mechanism associated with spermatozoa rosette‐type agglutination provoked by PFOS and PFOA. Furthermore, they underscore the need to delve more deeply into the mechanisms that govern agglutinate formation during spermatozoa capacitation physiology to devise improved, targeted therapeutic strategies for male infertility and enhance animal reproduction.